Komposisi botani dan produksi hijauan serta kapasitas tampung padang penggembalaan alam di desa Bena Kecamatan Amanuban Selatan Kabupaten Timor Tengah Selatan - Agryani Debora Selan; Yoakim Harsuto Manggol; Stefanus Tani Temu (Jurnal Peternakan Lahan Kering, 2019)
The study was carried out on natural pasture in Desa Bena Kecamatan Amanuban Selatan Kabupaten Timor Tengah Selatan. The study aimed at botany composition, forage production, and carry capacity of early dry season of the natural pasture. Survey by on the field measurement method was used in the study. Forage production was estimated with Actual Weight Estimate methodusing 1 m x 1 m frame square tool. Collected data were tabulated and calculated to obtain botany percentage and composition, forage production, and carry capacity. Statistical analysis showed that natural pasture in Desa Bena Kecamatan Amanuban Selatan Kabupaten Timor Tengah Selatan has Summed Dominance Ratio (SDR) grass71.65%, legume 27.87%, and weeds 0.48%, with forage production 727.75, Kgfresh/Hapr 53.18 kg DM in dry season. It is estimated that the natural pasture can carry 0.436 AU/Ha/year. Based on the botany composition, it is recomended that natural pasture in Desa Bena Kecamatan Amanuban Selatan Kabupaten Timor Tengah need legume introduction to maximize the carry capacity of the pasture.